Structural equation modelling of users’ assessment of affordable housing in developing cities - AKINYODE, Babatunde Femi; JELILI, Musibau Omoakin; ODUNOLA, Olaitan Olutayo (Economic and Environmental Studies, 2020)
This study investigated the users’ assessment of affordable housing in developing cities among the residents of Ibadan urban centre. Affordable housing entails users having access to quality housing at reasonable prices, obtaining it, maintaining the ability to meet other basic costs of living and to stay in it without any problem in order to promote good health, accessibility, convenience and environment that is free from crime and violence. The study developed a theoretical model that links users’ assessment to the affordable housing. Questionnaire was developed and administered to 494 residents in the five local government areas within Ibadan. The data was analysed using statistical packages SPSS and AMOS version 22. Exploratory factor analysis and confirmatory factor analysis techniques were applied to evaluate the users’ assessment of affordable housing. The structural equation modelling as the validated measuring tools was employed to validate the theoretical model. The finding indicated that detailed examination, assessment and critical reflection of users on their affordable housing is an important step towards designing policies to improve affordable housing that is accessible to users. The authors are of the opinion that strategies through the employment of suitable housing policy are needed to address the challenge of existing affordable housing in developing cities.